Kotowaza dalam Kajian Linguistik Kognitif: Penerapan Gaya Bahasa Metonimi (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2017)
This paper analyzes kotowaza using metonymy through the study of cognitive linguistic. The background of this research is the difficulty of understanding the correlation between the meanings of the kotowaza on foreign learners because of cultural differences and lack of dictionaries that support the process of understanding kotowaza deeply. The purpose of this research is to understand kotowaza deeply, determine the correlation between lexical and figurative meaning of Japanese proverbs using metonymy based on the study of cognitive linguistics. The method used is a qualitative method in approach of cognitive linguistics. At the end of the study, it was concluded that the metonymy that can be used to analyze the correlation between lexical and figurative meaning of proverbs are causality metonymy and method-purpose metonymy. Meanwhile, the proverbs that can be analyzed using a metonym associated with the brand and nicknames are not found.